Arterial Hypertension Secondary to Renal Artery Stenosis in a Child: Diagnosis and Management, a Case Report - Barbosa, Isadora Langoni Amorim; Cabral, Tayenne do Vale; Carraro, Mariana; Curi, Mariana Castro Loureiro Borges e (Cardiology and Cardiovascular Medicine, 2021)
Arterial hypertension (AH) in children up to 13 years old is defined as systolic blood pressure, diastolic blood pressure, or both above the 95th percentile for their age, sex, weight, and height by percentile. In children older than 13, it is defined by values greater than or equal to 130 × 80 mmHg. A diagnosis of Takayasu's arteritis is only established as set forth in the EULAR/PRINTO/PRES diagnostic criteria (2008) the mandatory criterion is an angiography of the aorta and its main branches or of the pulmonary arteries showing an aneurysm, dilatation, stenosis, occlusion, or thickening of the vessel wall, while discarding other possibilities. Additionally, at least one of these minor criteria must be present pulse deficit or claudication; blood pressure (BP) discrepancy in any of the four limbs; cardiac or arterial murmurs, systemic arterial hypertension; and acute-phase laboratory reactions (erythrocyte sedimentation rate > 20 mm or C-reactive protein above the reference value). To highlight the importance of BP evaluation in pediatric outpatient clinics, aiming for an early diagnosis to allow rapid management and a reduction of morbidity and mortality in pediatric patients. A previously healthy 8-year-old girl developed AH associated with headache and arthralgia. A diagnostic investigation was conducted, concluding that the AH was secondary to a stenosis of a renal artery, with a probable differential diagnosis of Takayasu's arteritis. An early and adequate clinical conduct causes an impact in reducing the morbidity and mortality of pediatric patients diagnosed with arterial hypertension and in maximizing their chances of recovery.